Exploring Learning Obstacle of Pre-Service Chemistry Student Towards Education for Sustainability on the Topic of Biodiesel: A Preliminary Study for Developing Didactic Design - Aldini Aulia; Hernani Hernani; Asep Supriatna (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to identify the learning obstacles experienced by preservice chemistry teachers in studying the biodiesel topic in the energy section. The research method employed is qualitative descriptive, with the instrument is interview guide sheet. Participants in this study were students of the program study of Chemistry Education. The result of the interviews with prospective chemistry teachers reveals that the primary learning obstacle related to the biodiesel topic are epistemological learning obstacle, with many students struggling to understand and apply concepts in depth. While students generally grasp the basic differences between renewable and non-renewable energy and the benefits of biodiesel, they lack detailed knowledge about biodiesel production processes and potential feedstocks. Additionally, there is a reliance on provided materials and insufficient initiative in seeking additional information. To address these challenges, it is essential to design more structured in learning experiences